Morality and Sociability - Hoyos, Luis Eduardo (2000)
The starting-point of this paper is the central idea of the moral meaning of human existence". It could be said that this idea is part of another one from Schopenhauer (he speaks about existence in general andnot only about human existence). and it tries to come to light in the philosophical project of the so-called "discursive ethics", although in a very different form. Itis referred critically to this form in the last section of the paper. The artícle is mainly concerned with a defense of the constitutive value which moral consciousness represents for the life of society, far from an ethical rationalist point of view.